The Effect of ESG Performance on Firm Value with Financial Performance as Mediation in Companies Listed on IDX ESG Leaders in 2020-2023 - Rizal Adriansyah Rusmana Rusmana; Ferikawita Magdalena Sembiring (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
The Indonesia Stock Exchange launched the ESG Leaders stock index on December 23, 2020, which contains 30 stocks that have the best ESG assessment and are not involved in controversy. Nevertheless, there has been a decline in the valuation of companies within the index as indicated by a drop in stock prices and Tobin's Q ratios. The primary aim of this study is to investigate the process of how the performance metrics related to environment, social responsibility, and corporate governance impact the value and financial performance of companies through mediation analysis. The study utilized quantitative approaches to analyze a group of businesses listed in the IDX ESG Leaders from 2020 to 2023. The sample selection involved deliberately selecting 25 companies for analysis. The researcher plans to study financial and corporate sustainability reports through panel data regression to analyze secondary data. The results indicate that ESG Performance may not directly influence the value of a company, but it could have a distinct effect on its financial performance. The impact of environmental performance on financial performance is beneficial and significant, whereas social and governance performance has a notably detrimental effect on financial performance. Moreover, a firm's value is positively influenced by financial performance, which can also act as a mediator for the impact of social and governance performance on firm value.